Do congenitally blind people have visual dreams? - Michael J. O. Andrade (Sleep Science, 2021)
The predominance of visual content in dreams raises a fundamental issue in the formation of images and for the construction of ideas based on the activity of the visual cortex in people with visual impairments. The central question for students of the visual system and for dream connoisseurs is: to what extent the absence or loss of vision will affect the sensory sensitivity for dream construction. Sensory modalities other than vision (tactile and auditory) can influence the functional development of the occipitotemporal visual system in the absence of visual stimulation early in life. What I mean is that blind individuals have significantly less visual capacity, but they also have an increase in the number of auditory, tactile, olfactory, and gustatory sound impressions.